SIGGRAPH Asia 2014 Technical Briefs 2014
DOI: 10.1145/2669024.2669042
|View full text |Cite
|
Sign up to set email alerts
|

Underwater reconstruction using depth sensors

Abstract: In this paper we describe experiments in which we acquire range images of underwater surfaces with four types of depth sensors and attempt to reconstruct underwater surfaces. Two conditions are tested: acquiring range images by submersing the sensors and by holding the sensors over the water line and recording through water. We found out that only the Kinect sensor is able to acquire depth images of submersed surfaces by holding the sensor above water. We compare the reconstructed underwater geometry with mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The use of infrared projectors, such as Kinect, has also been tested underwater [ 75 ]. The attempt confirmed that the absorption of the infrared spectrum is too strong to reach distances greater than a few centimeters.…”
Section: Sensors and Technologiesmentioning
confidence: 99%
“…The use of infrared projectors, such as Kinect, has also been tested underwater [ 75 ]. The attempt confirmed that the absorption of the infrared spectrum is too strong to reach distances greater than a few centimeters.…”
Section: Sensors and Technologiesmentioning
confidence: 99%
“…The base algorithm used in this work is an implementation of KinectFusion [ 15 ], a real-time 3D mapping and tracking method developed for use with the Microsoft Kinect and similar RGBD sensors. Although there has been some research done on using range sensors in water [ 37 , 38 ], the results have been of very limited practical use due to difficulties in dealing with light refraction and attenuation, which means that even in good visibility the maximum achievable range is about 20 cm. To overcome this limitation, the work presented in this paper relies on two synchronised colour cameras producing a stereoscopic image pair for disparity estimation.…”
Section: Algorithmmentioning
confidence: 99%
“…However, due to the infrared wavelength of the laser pattern projector the achievable range is limited to less than 30 cm (Dancu et al, 2014). Fringe projection has been applied successfully to acquire very detailed scans with high precision of small underwater objects (Törnblom, 2010;Bräuer-Burchardt et al, 2015).…”
Section: Underwater Laser Scanningmentioning
confidence: 99%